The role of self-reported fear and disgust in the activation of behavioral harm avoidance related to medical settings - Birkás, Béla; Kiss, Botond; Coelho, Carlos M.; Zsidó, András N. (Frontiers in Psychiatry, 2023)
Introduction Although adaptive defense mechanisms are useful in helping us avoid getting injured, they are also triggered by medical interventions and procedures, when avoidance is harmful. A body of previous results showed that both fear and disgust play a pivotal role in medical avoidance. However, the underlying mechanisms are not fully understood. Thus, the aim of the current study was to examine the effects of experience, perceived control, and pain on medical avoidance with disgust and fear as mediating factors from an evolutionary perspective. Methods We assessed participants' knowledge of and experience with medical procedures, former negative medical experiences, and health-related information; their life history strategy variation; pain-related fear and anxiety of medical procedures; perceived control over emotional reactions and extreme threats; disgust sensitivity; blood-injury-injection phobia and medical treatment avoidance. Results We found that more knowledge, experience, and a slower life strategy were linked to a greater level of perceived control and attenuated emotional reactions. Further, better ability to control affective and stress reactions to negative experiences was linked to reduced disgust and fear of pain, and thus might mitigate the level of perceived threat, and diminish fear and disgust reactions. Discussion More knowledge and experiences, better perceived control together with reduced disgust and fear of pain can decrease the probability of avoiding medical situations. Implications to treatment are discussed. Results support the importance of targeting these contextual factors in prevention to increase the likelihood of people attending regular screenings or seeking medical care when needed.